Captain Underpants and the terrifying return of Tippy Tinkletrousers the ninth epic novel - Pilkey, Dav 1966- (New York Scholastic, Inc, 2016)
After being sent to jail for the rest of their lives, George and Harold are taken on a trip back in time by Tippy Tinkletrousers back to their Kindergarten days where they must deal with their bully without the help of Captain Underpants.
Keywords: Captain Underpants (Fictitious character) -- Fiction; Time travel -- Fiction; Bullies -- Fiction; Schools -- Fiction; Heroes -- Fiction; Humorous stories; Humorous fiction